The Effect of Work Motivation and Perception of College Support on Organizational Commitment and Organizational Citizenship Behavior in BKPSDM, Tangerang District - Iskandar Nordat; Burhanudin Tola; Mahmudin Yasin (Bright Institute, 2022)
This study aims to analyze the effect of employee motivation, perceptions of colleague support, and organizational commitment to organizational citizenship behavior in BKPSDM, Tangerang District. This study uses an Associative Quantitative approach, namely by studying the causal relationship between independent variables and dependent variables. The data collection methods used were survey methods and structural equation modeling (SEM) analysis techniques with SMART PLS 3 software. The population in this study were all employees in the BKPSDM environment and civil servants managing personnel within the OPD area of Tangerang Regency, as many as 140 people. While the sample used in this study were 100 people. The result showed that Organizational Commitment has significant direct effect on Organizational Citizenship Behavior, Perceived Coworker Support has significant direct effect on Organizational Commitment, Work Motivation has significant direct effect on Organizational Commitment, Work Motivation has significant indirect effect on Organizational Citizenship Behavior through Organizational Commitment. Meanwhile, Perceived Coworker Support has not significant direct effect on Organizational Citizenship Behavior, Work Motivation has not significant direct effect on Organizational Citizenship Behavior, and also Work Motivation has not significant indirect effect on Organizational Commitment through Organizational Citizenship Behavior.